Molecular operational taxonomic units of mosquitoes (Diptera: Culicidae) collected in high Andean mountain ecosystems of Antioquia, Colombia (2017)
ABTRACT : Accurate taxonomic identification of highland mosquito species may be complicated because of the lack of comprehensive regional morphological keys and taxonomic specialists, particularly for mosquitoes of medical or ecological importance. We applied a multi-locus approach to explore the diversity of genera/species collected, to define the Molecular Operational Taxonomic Units (MOTUs) and to perform phylogenetic clustering. Twenty MOTUs and three single sequences were revealed from 78 concatenated cox1 + ITS2 sequences, and the species name was allocated for five of these. This study provides molecular taxonomic information of culicid fauna present in high Andean mountain ecosystems in Antioquia, Colombia. However, future morphological and integrative taxonomic studies should be conducted to achieve the specific identity of all detected MOTUs.